A Bi‐Sheath Fiber Sensor for Giant Tensile and Torsional Displacements. (19th July 2017) - Wang, Run; Jiang, Nan; Su, Jian; Yin, Qu; Zhang, Yue; Liu, Zhongsheng; Lin, Haibao; Moura, Francisco A.; Yuan, Ningyi; Roth, Siegmar; Rome, Richard S.; Ovalle‐Robles, Raquel; et al.
Abstract : Current research about resistive sensors is rarely focusing on improving the strain range and linearity of resistance–strain dependence. In this paper, a bi‐sheath buckled structure is designed containing buckled carbon nanotube sheets and buckled rubber on rubber fiber. Strain decrease results in increasing buckle contact by the rubber interlayer and a large decrease in resistance. The resulting strain sensor can be reversibly stretched to 600%, undergoing a linear resistance increase as large as 102% for 0–200% strain and 160% for 200–600% strain. This strain sensor shows high linearity, fast response time, high resolution, excellent stability, and almost no hysteresis. Abstract : Novel bi‐sheath strain sensors for tensile and torsional strain are fabricated by hierarchically buckling an aligned carbon nanotube sheath on a buckled elastomer‐coated rubber fiber. The contact area between adjacent nanotube buckles decreases with increasing stretch to provide 160% increase in resistance during 600% sensor elongation, which is fast in response, low in hysteresis, and high in cycle life.